A Pharmaceutico-Analytical and Antimicrobial Study of Trivargtrityadi Yoga (TTY) (International Journal of Ayurveda and Pharma Research, 2022)
In current scenario herbal formulations containing natural ingredients is more acceptable in public belief than chemical based synthetic formulations due to their safety and efficacy in reducing dental caries, pyorrhoea and preventing other dental and oral issues to which this generation is prone to. Clinically more effective and tolerable treatments should improve patient compliance with oral hygiene practices, further supporting medical professionals' efforts to avoid disease. Controlling the creation of dental plaque is the most efficient method of preventing the onset of dental disease. Microbes have an impact on its formation. Ayurveda recommends some daily use therapeutic procedures for the prevention and maintenance of oral health. These include: Pratisarana (gentle massage over tissue), Dant Dhavani (brushing), Jivha Lekhana (tongue scrapping) and Gandoosha (gargling) or oil pulling. The present study focused on preparation and validation of the classical formulation Trivargtrityadi yoga (TT yoga) which mentioned in Ashtang Sangraha by Acharya Vagbhata described in Dantadhawanacharya. It Contains Triphala, Trikatu, Trijatak and Kuth. These extracts have a variety of beneficial characteristics, including those that are anti-cancer, anti-fungal, and anti-ulcer, anti-caries, anti-bacterial and wound healing. The preparation of the formulation in accordance with traditional references and evaluation of its analytic and antibacterial properties are the objectives of this study.